2015
DOI: 10.1186/s12875-015-0359-x
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for interventions, co-occurrence and risk factors for unhealthy behaviours in patients consulting for routine primary care: results from the Pre-Empt study

Abstract: BackgroundSmoking, excessive drinking, lack of exercise and a poor diet remain key causes of premature morbidity and mortality globally, yet it is not clear what proportion of patients attending for routine primary care are eligible for interventions about these behaviours, the extent to which they co-occur within individuals, and which individuals are at greatest risk for multiple unhealthy behaviours. The aim of the trial was to examine ‘intervention eligibility’ and co-occurrence of the ‘big four’ risky hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The main reason for study exclusion was the lack of investigation of co-occurrence or of clustering between risk behaviours. Thirty-seven studies [ 3 , 14 – 50 ] met the inclusion criteria and were included in the review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason for study exclusion was the lack of investigation of co-occurrence or of clustering between risk behaviours. Thirty-seven studies [ 3 , 14 – 50 ] met the inclusion criteria and were included in the review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (thirteen datasets) assessed factors associated with engaging in multiple risk behaviours. Six included adult populations [ 3 , 14 , 15 , 21 , 46 , 50 ], three (four datasets) young adults [ 31 , 44 , 47 ], one students [ 36 ], one at risk populations [ 49 ] and one older adults [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In a recent UK general practice trial, over 90% of patients who were identified as consuming too much alcohol also had a poor diet, did too little exercise, or smoked. 33 So, how, when, or why should practitioners with limited time prioritise alcohol over other potential targets for prevention? And would simultaneously addressing behavioural risks, if this could be arranged, be more or less effective than tackling them individually?…”
Section: Generalisability and Implementation Problemsmentioning
confidence: 99%
“…In most societies, professionals find it easier to address and offer helpful advice in relation all other unhealthy lifestyles except for alcohol abuse. People with alcohol problems often also present with other unhealthy lifestyles, and studies have shown that unhealthy lifestyle factors tend to cluster together (Randell et al 2015). Hence, using admission to the hospital coupled with a more generalized approach to asking patients about their alcohol consumption might help to identify individuals with harmful alcohol use and dependence.…”
Section: Introductionmentioning
confidence: 99%